O'Brien, Aloysius 8. Interview about hay making work. - Shawyer; Jo (1992)
The topics concentrate on the hay making and hay storing. "00:00 – 05:00 bring the hay to the barrack; 05:00- 10:00 lay the hay in the mow; bench; kay knife; 10:00 – 15:00 barrack building; posts for hay barrack; 15:00- 20:00 hay press; “interval”, inheritance in land; 20:00 - 25:00 building hay cock; cap of a hay 25:00- 30:04 the meaning of hay making "